Dual purpose wheat and barley for human food and livestock feed in India - International Livestock Research Institute (International Livestock Research Institute, 2015)
This film reports on work by the Tata Founation supported 'enhancing livelihoods through livestock knowledge systems' (ELKS) project. It explains how ILRI and the Himmotthan foundation have been increasing the availabillity of fodder for dairying in Uttarakhand in India.